Neutralizing Antibodies and Cellular Immune Responses Against SARS-CoV-2 Sustained One and a Half Years After Natural Infection - Yan, Li-na; Liu, Pan-pan; Li, Xu-gui; Zhou, Shi-jing; Li, Hao; Wang, Zhi-yin; Shen, Feng; Lu, Bi-chao; Long, Yu; Xiao, Xiao; Wang, Zhen-dong; Li, Dan; et al. (Frontiers in Microbiology, 2022)
Background: COVID-19 has caused more than 2.6 billion infections and several million death since it outbreak two years ago. We know very little about the long-term cellular immune responses and the kinetics of neutralizing antibodies (NAbs) to SARS-CoV-2 because it has emerged only recently in the human population. Methods: We collected blood samples from individuals who were from the first wave of COVID-19 epidemic in Wuhan between December 30, 2019 and February 24, 2020. We analyzed NAbs to SARS-CoV-2 using pseudoviruses and IgG antibodies to SARS-CoV-2 spike (S) and nucleocapside (N) protein using enzyme-linked immunosorbent assay in patients’ sera and determined SARS-CoV-2 specific T-cell responses of patients with ELISpot assays. Results: We found that 91.9% (57/62) and 88.9% (40/45) of COVID-19 patients had NAbs against SARS-CoV-2 in a year (10-11 months) and a year and half (17-18 months), respectively, after the onset of illness, indicating that NAbs against SARS-CoV-2 waned slowly and possibly persisted over a long period of time. Over 80% patients had IgG antibodies to SARS-CoV-2 S and N protein a year and half after illness onset. Most patients also had robust memory T-cell responses against SARS-CoV-2 a year and half after illness. Among the patients, 95.6% (43/45) had an IFN-γ-secreting T-cell response and 93.8% (15/16) had an IL-2-secreting T-cell response. The T-cell responses to SARS-CoV-2 is positively correlated with antibodies (including neutralizing antibodies, IgG antibodies to S and N protein) in COVID-19 patients. 80% (4/5) of neutralizing antibody negative patients also had SARS-CoV-2-specific T-cell response. After long-term infection, protective immunity was independent of disease severity, sex, and age. Conclusions: We concluded that SARS-CoV-2 infection elicited a robust and persistent neutralizing antibody and memory T-cell response in COVID-19 patients, indicating that these sustained immune responses, among most SARS-CoV-2 infected people, may play crucial role in protection against reinfection.